Consumo de drogas y conducta violenta de un joven de 24 años privado de la libertad del Crs de Babahoyo - Placencia Gavilanes, Misael Edison (2021)
The current case study has its origin in the problem of violent behavior due to drug use, specifically “cannabis”. This approach will allow to establish the effects that are generated in these cases; having as object of study a 24-year-old deprived of liberty from the CRS of Babahoyo and how cannabis use affects his behavior. These types of disorders are common in the prison social environment, due to an addictive dopamine gratification, which causes a response from the endocannabinoid system and its psychoactive interpretation; This being a non-experimental study, texts and bibliography of previous works related to addictive behavior were used. It is intended to achieve the cognitive restructuring of automatic thoughts, in which the principles and skills acquired Cognitive Behavioral will be applied, in the execution of the evaluative process, distinctive methodology and techniques were used such as: the HPT personality test, ASSIST addiction test V3.0 and the Salamanca screening test, which corroborated the information on signs or symptoms in abstinence: among the main conclusions obtained in the process, it was confirmed that it is not only drugs that are the causes of violent behaviors, but the personality itself and mental schemas of the subject, acquired throughout his life and the risk factors present in the social confinement center in which the patient is confined.